Suicidal Ideation and Behavior Among Congolese Refugees in Rwanda: Contributing Factors, Consequences, and Support Mechanisms in the Context of Culture - Ingabire, Chantal Marie; Richters, Annemiek (Frontiers in Psychiatry, 2020)
Concern in one of the five camps for Congolese refugees in Rwanda about suicide attempts and death in 2017 as well as research data pointing to a relatively high incidence of suicidal ideation in this and a second camp in the same period provided the impetus for this exploratory qualitative study. The study explored factors contributing to suicidal ideation, attempts and death; existing support and referral mechanisms; and recommendations regarding prevention and care strategies. Between July and September 2018, 10 focus group discussions were conducted with refugees and representatives of stakeholders working in the camp, and 21 in-depth interviews with refugees who reported suicidal ideations in a previous quantitative survey, two refugees who attempted suicide, and family members of those who reported suicidal ideas, attempted suicide or committed suicide. Findings suggest that while all refugees have suffered from war and violence in Congo and experienced traumatic events before arriving in Rwanda, the pathway to suicidal ideations was often triggered by the circumstances related to their current situation in the context of refugeehood. Almost all respondents who experienced suicide ideations and/or attempted to commit suicide reported poor mental health, a low sense of connectedness/belonging and a high level of perceived burden, which were greater than their desire to live. Family conflicts were found to be an important starting point leading to suicidal ideations and in some cases to suicide attempts and deaths. For the adult population, family conflicts often resulted from the cultural and legal changes experienced after fleeing their home country, misunderstandings of Rwandan gender equality policies, and disagreements about family income management. For youth, a lack of hope for the future was found among boys and girls, and for some girls, suicidal ideations were triggered by poor interpersonal/family relationships due to unwanted pregnancies. Family, community and faith-based support mechanisms were reported as being available but not always culturally sensitive. Psychosocial support services should be improved and expanded to ensure effective psychosocial recovery. Family conflicts related to a lack of family communication and a misconception of gender equality policies should be tackled with attention to the cultural factors involved.